2020
DOI: 10.3389/fonc.2020.01457
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of Esophageal Squamous Cell Carcinoma in an Indian Cohort

Abstract: Esophageal squamous cell carcinoma (ESCC) is the most common histological subtype of esophageal cancer in India. Cigarette smoking and chewing tobacco are known risk factors associated with ESCC. However, genomic alterations associated with ESCC in India are not well-characterized. In this study, we carried out exome sequencing to characterize the mutational landscape of ESCC tumors from subjects with a varied history of tobacco usage. Whole exome sequence analysis of ESCC from an Indian cohort revealed severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 86 publications
1
24
1
Order By: Relevance
“…Such a strategy has previously been used to identify a mutational signature present in renal cell carcinomas which implicated an environmental exposure to aristolochic acid in a specific geographic location 12 . Whilst there have been previous studies which have provided a comprehensive overview of the ESCC genome, some including mutational signatures analysis, many of these are limited to whole exome sequencing or cases from high incidence regions only 1320 . Furthermore, a comprehensive analysis of associations between mutational signatures and ESCC risk factors across multiple regions with varying incidence has not been described previously.…”
Section: Mainmentioning
confidence: 99%
“…Such a strategy has previously been used to identify a mutational signature present in renal cell carcinomas which implicated an environmental exposure to aristolochic acid in a specific geographic location 12 . Whilst there have been previous studies which have provided a comprehensive overview of the ESCC genome, some including mutational signatures analysis, many of these are limited to whole exome sequencing or cases from high incidence regions only 1320 . Furthermore, a comprehensive analysis of associations between mutational signatures and ESCC risk factors across multiple regions with varying incidence has not been described previously.…”
Section: Mainmentioning
confidence: 99%
“…Our analysis illustrated that non-silent protein-coding mutation profiles distributed across ESCC cell lines and patient tissues are heterogeneous and diverse, with TP53, TTN, KMT2D, CSMD3, DNAH5, MUC16, and DST being the most frequently mutated genes. These observations are supported by recent research [39,40]; however, with the exception of TP53, the exact role of these mutated genes in ESCC has not been clearly elucidated. Further research is needed to confirm whether these mutated genes contribute to ESCC carcinogenesis.…”
Section: Tp53 Mutation Heterogeneity In Esccmentioning
confidence: 66%
“…In addition, cumulative evidences suggest that changes in SYNE1 expression levels, somatic mutations, promoter methylation level, and single-nucleotide polymorphisms are related to the occurrence and development of lung cancer (20), oral cancer (21), hepatocellular carcinoma (22), and gastric cancer (23). Furthermore, SYNE1 was found to be frequently mutated in an Indian ESCC cohort (24). In the present study, we reported SYNE1 mutations associated with worse prognosis in patients with ESCC, which is consistent with a previous report of patients with clear cell renal cell carcinoma showing that SYNE1 mutations correlate with a higher tumor mutation burden and poorer outcomes (25).…”
Section: Discussionmentioning
confidence: 99%